AB0350 Rituximab Seems Outstanding Biological Option in Late Onset Rheumatoid Arthritis: Hur-Bio Real Life Results. (15th July 2016) - Kilic, L.; Erden, A.; Sari, A.; Armagan, B.; Karadag, O.; Akdogan, A.; Apras Bilgen, S.; Kiraz, S.; Ertenli, I.; Kalyoncu, U.
Abstract : Background: Rheumatoid arthritis (RA) can be categorized into late-onset RA and young-onset RA. Age at disease onset may implicate on disease activity, disease severity, comorbidity and also may have an impact on physicians' treatment choices. Objectives: The aim of this study was to assess clinical and laboratory features, disease activity, response, and biological treatment choices according to late-onset RA and young-onset RA patients. Methods: Hacettepe University Biologic Registry (HUR-BIO) is a single center biological registry since 2005. HUR-BIO biological dataset included demographic and clinical data and disease activity parameters. A total of 1087 (79.4% female) patients from the HURBIO registry were analyzed. Patients were categorized into two groups: young-onset RA (n=990, <60 years of age) and late-onset RA (n=97, ≥60 years of age) at disease onset. DAS-28 remission (<2.6) and low disease activity (<3.2) were assessed at last outpatient visit. Results: The female gender was similar in both age group (77.3% vs. 79.6%, p>0.05). Mean age of patients were 71.4±6.0 years in late-onset RA and 51.6±11.7 years in young-onset RA group. The median age at diagnosis of patients were 64 (range 60–85) years in late-onset RA and 40 (range17–59) years in young-onset RA patients. Mean disease duration between diagnosis of RA and first biologic therapy was longer in young-onset RA patients [7.7±7.3 vs. 2.7±2.6 years, p<0.001], but mean biologic duration was similar in both groups [29.9±27.5 vs. 38.4±37.1 months, p>0.05]. Rheumatoid factor and anti-citrullinated peptides positivity in late-onset RA and young-onset RA patients were; 56.2% vs. 63.8% (p>0.05) and 45.9% vs. 63.2%, p=0.008, respectively. At the baseline level, anti-TNF (61 (61.9%) vs. 827 (73.6%), p=0.014) drugs were less frequently used in late-onset RA, rituximab (21 (21.6%) vs 111 (11.3%), p=0.003) was more frequently used in late-onset RA, and abatacept (16 (16, 5%) vs. 148 (15, 1%), p>0.05) was used similar in both group. Change in DAS-28 score was similar [1.55±1.14 vs. 1.79±1.45 (p>0.05)], in late-onset RA and young-onset RA patients. Remission (29.5% vs. 38.6%, p>0.05) and low disease activity (52.5% vs. 55.4%, p>0.05) were similar in late-onset RA and young-onset RA patients. Biological switch ratio was significantly lower in late-onset RA group, 18.6% vs. 35.2%, p<0.001. Conclusions: Age may influence the clinician choice based on the efficacy and safety profile. Biologic drugs are effective in late-onset RA, as well. Rituximab was relatively more preferred in late-onset RA patients; may be related with administration of every 6 months and safety profile in malignancy risk. Patient and physician opinion on these choices should be evaluated in further studies. Disclosure of Interest: None declared